Rebel Governance as State-Building? Discussing the FARC-EP's Governance Practices in Southern Colombia - Gutiérrez, José A. (PARTECIPAZIONE E CONFLITTO, 2022)
Rebel governance practices are often conflated with state-building, as if the former were the embryonic stages of the latter. This association is not necessarily accurate. Some rebels do not aim at replacing the state with another of their own. It also fails to reflect the complex configuration of political power in conflict areas. I comparatively analyze the governance practices of the FARC-EP in six villages in Colombia. Considering the state's presence in those territories and the social background of both rebels and their constituencies, I describe two broad patterns: armed advocacy and substitute state. In none of the cases was the state completely challenged, and there were many overlaps as the rebels used the state structure to advance their cause, in the process inadvertently expanding the infrastructural power of the State they confronted. It is only in this sense that the FARC-EP could be described as unconsciously contributing to state-building, not in the sense that through their governance practices they were laying the foundations for their own state apparatus. This hybrid and ambiguous situation illustrate the importance of understanding the overlapping regimes of territorial authority in conflict situations, as opposed to expecting clear-cut boundaries and monopolies (of violence, power) that rarely occur.